2018
DOI: 10.3390/s18093021
|View full text |Cite
|
Sign up to set email alerts
|

Edge Computing Based IoT Architecture for Low Cost Air Pollution Monitoring Systems: A Comprehensive System Analysis, Design Considerations & Development

Abstract: With the swift growth in commerce and transportation in the modern civilization, much attention has been paid to air quality monitoring, however existing monitoring systems are unable to provide sufficient spatial and temporal resolutions of the data with cost efficient and real time solutions. In this paper we have investigated the issues, infrastructure, computational complexity, and procedures of designing and implementing real-time air quality monitoring systems. To daze the defects of the existing monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 37 publications
(41 reference statements)
0
31
0
Order By: Relevance
“…However, 14 studies (35%) used MQ series sensors (MQ135, MQ6, MQ4, MQ7, MQ9, MQ5, MQ2, MQ3) for measuring gaseous pollutants. Furthermore, 25% of the studies [ 61 , 63 , 68 , 70 , 78 , 79 , 81 , 82 , 86 , 90 ] used the MQ135 multi-gas sensor. The primary disadvantage of MQ series sensors is that they require field calibration.…”
Section: Resultsmentioning
confidence: 99%
“…However, 14 studies (35%) used MQ series sensors (MQ135, MQ6, MQ4, MQ7, MQ9, MQ5, MQ2, MQ3) for measuring gaseous pollutants. Furthermore, 25% of the studies [ 61 , 63 , 68 , 70 , 78 , 79 , 81 , 82 , 86 , 90 ] used the MQ135 multi-gas sensor. The primary disadvantage of MQ series sensors is that they require field calibration.…”
Section: Resultsmentioning
confidence: 99%
“…Idrees et al [48] closely observed the challenges associated with IAP and developed an Arduino based platform for real-time IAQ monitoring systems. They initiated steps toward the detailed investigation of factors such as computational complexity, infrastructure, issues, and procedures for efficient designing.…”
Section: Indoor Air Quality Monitoring (Iaqm) Systemsmentioning
confidence: 99%
“…Experts reveal that the IoT system can monitor a large number of parameters, even without compromising system performance. Studies carried by Idrees et al [48] and Sivasankari et al [49] gave a new edge to the IAQ monitoring systems with impactful IoT architecture design. However, very few researchers in the past few years have worked on prediction systems in the field of IAQ monitoring.…”
Section: Iot Based Systemsmentioning
confidence: 99%
“…The automation of the phase alignment and measurement processes has the advantage of increasing both speed and reliability, as well as reducing operation costs compared to manual execution [5]. That is why, for the operation of the system, the Arduino YUN [46] platform was used.…”
Section: Phase Alignment and Data Transmission Interfacementioning
confidence: 99%
“…Device miniaturization has been key to the development of innovative sensing technology with application in different fields [1], ranging from biology and medicine [2,3], to environmental monitoring [4][5][6], or limnology and civil structural monitoring [7][8][9]. Therefore, the interest in new large scale integrated systems including sensing technology is growing substantially, since they make it possible to carry out the same analysis usually performed by traditional sophisticated equipment but with the advantage of reduced size, power, and cost.…”
Section: Introductionmentioning
confidence: 99%